Confronting the challenge: a regional perspective by the Latin American pediatric infectious diseases society (SLIPE) expert group on respiratory syncytial virus—tackling the burden of disease and implementing preventive solutions - Debbag, Roberto; Ávila-Agüero, María L.; Brea, José; Brenes-Chacon, Helena; Colomé, Manuel; de Antonio, Rodrigo; Díaz-Díaz, Alejandro; Falleiros-Arlant, Luiza Helena; Fernández, Gerardo; Gentile, Angela; Gutiérrez, Iván Felipe; Jarovsky, Daniel; et al. (Frontiers in Pediatrics, 2024)
Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory infections in children around the world. The post-pandemic era has resulted in a notable increase in reported cases of RSV infections, co-circulation of other respiratory viruses, shifts in epidemiology, altered respiratory season timing, and increased healthcare demand. Low-and middle-income countries are responsible for the highest burden of RSV disease, contributing significantly to health expenses during respiratory seasons and RSV-associated mortality in children. Until recently, supportive measures were the only intervention to treat or prevent RSV-infection, since preventive strategies like palivizumab are limited for high-risk populations. Advances in new available strategies, such as long-acting monoclonal antibodies during the neonatal period and vaccination of pregnant women, are now a reality. As the Regional Expert Group of the Latin American Pediatric Infectious Diseases Society (SLIPE), we sought to evaluate the burden of RSV infection in Latin America and the Caribbean (LAC) region, analyze current strategies to prevent RSV infection in children, and provide recommendations for implementing new strategies for preventing RSV infection in children in LAC region.